2019
DOI: 10.1590/1414-431x20187809
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic cardiomyopathy: the liver affects the heart

Abstract: Cirrhotic cardiomyopathy historically has been confused as alcoholic cardiomyopathy. The key points for diagnosis of cirrhotic cardiomyopathy have been well explained, however this entity was neglected for a long time. Nowadays the diagnosis of this entity has become important because it is a factor that contributes significantly to morbidity-mortality in cirrhotic patients. Characteristics of cirrhotic cardiomyopathy are a hyperdynamic circulatory state, altered diastolic relaxation, impaired contractility, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 85 publications
0
47
0
4
Order By: Relevance
“…Cirrhotic cardiomyopathy is a clinical entity with serious impact on the evolution and prognosis of patients with liver disease [10]. Since it is usually under-diagnosed, the management of these patients is based on management of cirrhosis and its complications alone [2]. While the condition remains asymptomatic in a resting state, due to decreased afterload (reduces vascular peripheral resistance), under stressful conditions (infections, exercise, hemorrhage) it can promote overt heart failure [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cirrhotic cardiomyopathy is a clinical entity with serious impact on the evolution and prognosis of patients with liver disease [10]. Since it is usually under-diagnosed, the management of these patients is based on management of cirrhosis and its complications alone [2]. While the condition remains asymptomatic in a resting state, due to decreased afterload (reduces vascular peripheral resistance), under stressful conditions (infections, exercise, hemorrhage) it can promote overt heart failure [25].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from 1953 [1], cirrhotic cardiomyopathy (CCM) has been defined as a separate entity in the spectrum of heart conditions, strictly related to liver damage. Since then, clinical and experimental trials have defined CCM as chronic cardiac dysfunction associated with liver cirrhosis, in patients without heart disease, irrespective of the etiology of cirrhosis [2]. From a physio-pathological perspective, CCM is characterized by a hyperdynamic state, with both diastolic and systolic ventricular dysfunction, prolonged ventricular depolarization and an inappropriate chronotropic response to stress [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated a change in cardiac contractility in cirrhosis, mainly a decrease in left ventricular contractility and relaxation, which is characteristic of cirrhotic cardiomyopathy, a condition that can be present in up to 50% of patients with cirrhosis. 31,32 After TIPS placement, there is an expected increase in pre-load as pooled splanchnic blood volume is redistributed to the central blood volume. There is also an increase in pulmonary arterial pressure from the increased central blood volume and from vasoactive and neurohumoral mediators directly shunted from the portal circulation into the systemic circulation.…”
Section: Cardiac Diseasementioning
confidence: 99%
“…There is also an increase in pulmonary arterial pressure from the increased central blood volume and from vasoactive and neurohumoral mediators directly shunted from the portal circulation into the systemic circulation. 31,33 Van der Linden et al 34 demonstrated an elevation in pulmonary artery pressure immediately after and 1 month following TIPS placement, concluding that TIPS placement in patients with preexisting pulmonary hypertension should be performed with caution.…”
Section: Cardiac Diseasementioning
confidence: 99%